1985
DOI: 10.1002/ijc.2910350206
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer risk in chronic atrophic gastritis: Statistical calculations of cross‐sectional data

Abstract: Relative risk (RR) and cumulative risk of gastric cancer (GCA) were calculated for different grades of atrophic gastritis (AG) of the antrum and body. Cross-sectional data on the occurrence of AG in a representative population sample (371 subjects), and Finnish Cancer Registry data on GCA were used in the calculations. The RR was increased significantly in severe AG of the antrum and the body (18.1 and 4.6 times, respectively), but not significantly in the less severe grades of AG. As a risk factor, severe ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
199
0
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(205 citation statements)
references
References 21 publications
4
199
0
2
Order By: Relevance
“…Several previous studies have demonstrated that the more advanced the stage of H. pylori-related CAG, the greater the cancer risk. 31,32,[40][41][42][43][44] Subjects with metaplastic gastritis, an end result of long-lasting H. pylori infection, are thus considered to be at particularly high risk of gastric cancer. Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have demonstrated that the more advanced the stage of H. pylori-related CAG, the greater the cancer risk. 31,32,[40][41][42][43][44] Subjects with metaplastic gastritis, an end result of long-lasting H. pylori infection, are thus considered to be at particularly high risk of gastric cancer. Indeed, our previous longitudinal cohort study found that a group of middle-aged male subjects with metaplastic gastritis based on 2 serum tests-negative results for H. pylori antibody and positive results on the PG test-displayed an annual cancer incidence rate of about 0.87%, meaning that 1 cancer developed in 11.5 subjects during every 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…An atrophic mucosa is considered not to provide a sufficient environment for H. pylori colonization [26]. However, mucosa with widespread atrophy is considered the most risky mucosa for carcinogenesis, and is also considered to be the precursor of intestinaltype gastric carcinoma [12][13][14]. Thus, patients with mild atrophy with H. pylori infection may represent the most important targets for H. pylori eradication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Since Warren and Marshall [6] first isolated H. pylori from the stomachs of patients with gastritis, numerous studies have demonstrated the relationship between H. pylori infection and the development of gastric cancer [7][8][9][10]. Now, H. pylori is regarded as a definite carcinogen [11] and as a trigger for the sequence of carcinogenesis, because there is strong evidence for H. pylori infection as a cause of chronic atrophic gastritis and intestinal metaplasia, two possible precancerous lesions [9,10,[12][13][14]. Our previous observations on the background mucosa of early-stage carcinoma of the GR also indicated an intimate association between atrophic gastritis and intestinal-type gastric carcinoma [2].…”
mentioning
confidence: 99%
“…The incidence of GCA is approximately twice as high in males as in females (Day, 1982), and the GCA incidence strongly increases with increasing age in both sexes (Day, 1982;Sipponen et al, 1984). Several follow-up and cross-sectional studies have further shown that the risk of GCA is approximately 3-4 times as high in subjects with, than in those without, AG, a risk which obviously increases with increasing grade of AG (Siurala et al, 1966;Cheli et al, 1973;Meister et al, 1979;Sipponen et al, 1985). Sex, age and AG may be independent risk factors for GCA.…”
mentioning
confidence: 99%